Antibody‐Negative Paraneoplastic Limbic Encephalitis, Parkinsonism, Hypothermia, and Narcolepsy Associated with Endometrial Carcinoma. Issue 2 (7th January 2020) - Brennan, Declan; Murphy, Olwen C.; Fearon, Conor; Brett, Francesca; Murray, Brian; Lynch, Tim
ABSTRACT: Background: We describe the clinical and neuropathological features of a patient with T‐cell‐mediated paraneoplastic limbic encephalitis, parkinsonism, hypothermia, and narcolepsy‐like presentation associated with endometrial carcinoma. Objectives: This patient with prominent parkinsonism and narcolepsy broadens the phenotype of known paraneoplastic syndromes and demonstrates the importance of investigation for occult malignancy even in the absence of paraneoplastic antibodies. Methods: This is a case report with diagnosis confirmed at postmortem. Results: Paraneoplastic antibodies were not detected. The initial improvement with immunosuppression was short lived, and postmortem neuropathological examination demonstrated encephalitis with predominant T‐cell infiltration affecting the hypothalamus and extending to the brainstem, suggestive of a paraneoplastic syndrome. Conclusions: Although the possibility of a novel antibody cannot be ruled out, consideration must also be given to recent demonstration of purely T‐cell‐mediated neuronal destruction in the context of paraneoplastic syndromes.